Is nest-site availability limiting Lesser Kestrel populations? A multiple scale approach (Ibis, 2005)
The Lesser Kestrel, a colonial migratory falcon, is one of the most endangered birds in Europe and, due to a sharp population decline across much of the breeding range, is globally threatened. The reasons for this decline are unclear, but reduced nest-site availability might be a major cause. To test this hypothesis we looked at nest-site availability within Portuguese colonies in rural and urban buildings. Nest holes were larger, longer, higher and older than unoccupied cavities. A typical nest cavity was approximately 29–30 cm long, 300–340 cm high and had an inner chamber 16.5–18 cm wide. Large-scale surveys of existing buildings in Portuguese villages suggested that 85% of sites lacked suitable nest cavities. The model for selection of buildings indicated that Lesser Kestrels prefer buildings with many roof and wall cavities, and that are surrounded by extensive cereal and fallow ﬁelds. The villages selected had many old buildings and monuments, were located in areas with few rivers, and a low percentage cover of cereal, olive groves and forest. The conservation implications of these results are discussed.